Sustained Response of Ibrutinib in a Patient with Waldenstrom Macroglobulinemia Presenting with Myasthenic Crisis as a Paraneoplastic Neurological Syndrome: A Case Report and Review of Literature - Anna Mira Lubis; Fitri Octaviana; Gabriella Anindyah; Agnes Stephanie Harahap (Acta Medica Indonesiana)
Paraneoplastic syndrome is a broad spectrum of signs and symptoms due to neoplasm, attributed to substances produced by tumor cells, or in response to it. Myasthenia gravis (MG) is a well-known paraneoplastic neurological syndrome (PNS), frequently associated with thymic abnormalities, but rarely reported in patients with lymphoplasmacytic lymphoma.